1993
DOI: 10.1093/carcin/14.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HPV-18 and nitrosomethylurea in the induction of squamous cell carcinoma

Abstract: A strong correlation exists between the presence of specific types of human papillomavirus (HPV) and the development of anogenital cancer, as well as significant epidemiologic evidence suggesting smokers are at increased risk of developing cervical, vulvar and/or anal carcinomas. Primary and human papillomavirus type 18 (HPV-8)-immortalized human keratinocytes were used to address the co-carcinogenic potential of HPV and nitrosomethylurea (NMU) in tumorigenesis. Only cells containing HPV-18 and treated with NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
1
26
0
3
Order By: Relevance
“…36,37 In addition, the combined action of HPV-18 and NMU in the induction of squamous cell carcinoma has been shown. 38 Our data on neoplastic transformation of HPV-18-immortalized HPE cells by exposure to NMU provides additional support for the theory that neoplastic conversion is a multistep process. This system may be useful in evaluating the carcinogenic potential of environmental chemicals for studying genes that are activated or suppressed in the multistep process leading to malignancy.…”
Section: In Vitro Human Cell Culture Models Js Rhimsupporting
confidence: 72%
“…36,37 In addition, the combined action of HPV-18 and NMU in the induction of squamous cell carcinoma has been shown. 38 Our data on neoplastic transformation of HPV-18-immortalized HPE cells by exposure to NMU provides additional support for the theory that neoplastic conversion is a multistep process. This system may be useful in evaluating the carcinogenic potential of environmental chemicals for studying genes that are activated or suppressed in the multistep process leading to malignancy.…”
Section: In Vitro Human Cell Culture Models Js Rhimsupporting
confidence: 72%
“…Because it appears that it is most important if patients with cancer are current smokers at the time of diagnosis, current smoking likely has a promotional effect at late stages of disease progression. Garrett et al 26 found that HPV-18-immortalized human keratinocytes treated with a low dose of a compound similar to N-nitroso compounds found in tobacco and a single exposure to TPA, a tumor promoter, were converted to a malignant phenotype. It also has been shown that nicotine inhibits apoptosis, which may promote tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that environmental and host-related cofactors act in conjunction with HPV to promote malignant progression of cervical lesions (7). It has been proposed that cigarette smoking among HPV-positive women is one of the cofactors which likely influences the risk for cervical cancer progression (15,21,27,38,41,50,52,54). Tobacco-specific polycyclic aromatic hydrocarbons such as benzo[a]pyrene (BaP) (31) and nitrosamines such as 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) (43), which are potent inducers of carcinogenesis (12,16,28), have been detected in the cervical mucus of women who smoke and exhibit cervical dysplasias (19,29,47).…”
mentioning
confidence: 99%
“…Quantitative levels of noncarcinogenic nicotine and its metabolite cotinine in cervical mucus were correlated with smoking intensity (29,47,48) and were shown to be concentrated more strongly in cervical mucus than in blood (17). Colocalization of HPV and cigarette smoke carcinogens in the cervix may present an opportunity for virus/ carcinogen interaction (15).…”
mentioning
confidence: 99%